2006
DOI: 10.1248/bpb.29.2327
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Plasma Glucagon-Like Peptide 2 Levels and Proliferative Makers in Small Intestinal Injury in Rats Induced by Methotrexate Administration

Abstract: Chemotherapy is an important primary and adjuvant therapy for cancer patients. The cytotoxicity of antineoplastic agents affects not only tumor cells but also rapidly proliferating normal cells, such as those of the gastrointestinal mucosa.1) Common complications of chemotherapy thus include stomatitis and enterocolitis.2) Methotrexate (MTX) is an antimetabolite drug that blocks the production of biologically active forms of folic acid. The major lesions resulting from its cytotoxic effects occur in bone marro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…These findings reveal a relationship between the GLP-2 level and intestinal adaptation. Previous studies showed that supplementation of enteral nutrients or exogenous GLP-2 induced an increase in plasma concentration of GLP-2 in neonatal piglets and rats with intestinal injury or short bowel syndrome [ 3 , 4 , 12 ]. Similarly, in the present study, injection of a high dose of GLP-2 significantly prevented the decline of basal levels of plasma GLP-2 and increased the GLP-2 above the weaning level.…”
Section: Discussionmentioning
confidence: 99%
“…These findings reveal a relationship between the GLP-2 level and intestinal adaptation. Previous studies showed that supplementation of enteral nutrients or exogenous GLP-2 induced an increase in plasma concentration of GLP-2 in neonatal piglets and rats with intestinal injury or short bowel syndrome [ 3 , 4 , 12 ]. Similarly, in the present study, injection of a high dose of GLP-2 significantly prevented the decline of basal levels of plasma GLP-2 and increased the GLP-2 above the weaning level.…”
Section: Discussionmentioning
confidence: 99%
“…14,17) In rats, methotrexate-induced gastrointestinal mucositis is characterized histologically by crypt loss, callus fusion and atrophy, capillary dilatation, and infiltration of mixed inflammatory cells. 15,18,19) These side effects necessitate dose reduction and discontinuation of selected cancer therapies, and increase healthcare costs, prolong hospital stays, increase re-admission rates, compromise patient nutritional status, impair patient quality of life, and are occasionally fatal. Thus, therapeutic agents that ameliorate chemotherapy-induced gastrointestinal mucositis are urgently required.…”
mentioning
confidence: 99%
“…13) RNA Extraction and RT-PCR Messenger RNA expression was quantified by real-time RT-PCR using a 7500 Fast Real-Time PCR system (Life Technologies, Applied Biosystems, Foster City, CA, U.S.A.) and PrimeScript One Step RT-PCR kit (TaKaRa Bio, Shiga, Japan), as previously described. 14) The following sense and antisense primers, respectively, were used: proglucagon, 5′-AAC AAC ATT GCC AAA CGT CA-3′ and 5′-CAA TGA ATT CCT TTG CTG CC-3′; GLP-2 receptor, 5′-CGG ATT CTG GAA ATT CTT C-3′ and 5′-CCC CAG GAA CCG GAA ATT CTT C-3′; IGF-1, 5′-AAG CCT ACA AAG TCA GCT CG-3′ and 5′-GGT CTT GTT TCC TGC ACT TC-3′; DPP-4, 5′-TCC CAA CTC CAG AGG ACA AC-3′ and 5′-CAG GGT TTG GAG TCT GAG-3′; TGF-β1, 5′-TGG CGT TAC CTT GGT AAC C-3′ and 5′-CGT GTT GAG CCC TTT CCA G-3′; TGF-β2, 5′-ATC GAT GGC ACC TCC ACA TAT G-3′ and 5′-GCG AAG GCA GCA ATT ATG CTG-3′; TGF-β3, 5′-AAG CGC ACA GAG CAG AGA ATC-3′ and 5′-AGT GTC AGT GAC ATC GAA G 3′; β-catenin, 5′-GCC AAG TGG GTG GCA TAG A-3′ and 5′-TCC CTG TCA CCA GCA CGA A-3′; the exchange protein activated by cAMP 1 (Epac1), 5′-GTG TTG GTG AAG GTC AAT TCT G-3′ and 5′-CCA CAC CAC GGG CAT C-3′; Epac2, 5′-TGT TAA AGT GTC TGA GAC CAG CA-3′ and 5′-AAA GGC TGT CCC AAT TCC CAG-3′; and glyceraldehyde 3-phosphate dehydrogenase, 5′-ATG TTC CAG TAT GAC TCC ACT CAC G-3′ and 5′-GAA GAC ACC AGT AGA CTC CAC GAC A-3′. The PCR products were calculated relative to glyceraldehyde 3-phosphate dehydrogenase.…”
Section: Methodsmentioning
confidence: 99%